PEMBUATAN GAME “SIX HORIAN” UNITY DENGAN VIRTUAL REALITY - Hartanto, William; Pragantha, Jeanny; Haris, Darius Andana (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
“Six Horian“ is a survival and horror virtual reality game for Android. In this game player must survive with three or four candles still lit within 166 seconds to advance to the next stage. This game use three-dimensional graphics. The game is created with the purpose of using gyro sensor on smartphone into the game, using google cardboard as external tool, and game developed with Unity. This game created by Unity game engine with C# as programming language. The testing was done with 3 methods which were blackbox testing. Alpha testing, and beta testing through 30 respondents. The beta testing showed that not many people has played Virtual Reality game using jogging in the spot as a controller.